Inside Cover: Synthesis, Chiral Separation, Absolute Configuration Assignment, and Biological Activity of Enantiomers of Retro‐1 as Potent Inhibitors of Shiga Toxin (ChemMedChem 7/2015). Issue 7 (July 2015) - Abdelkafi, Hajer; Michau, Aurélien; Clerget, Alexandra; Buisson, David‐Alexandre; Johannes, Ludger; Gillet, Daniel; Barbier, Julien; Cintrat, Jean‐Christophe
<x xml:space="preserve">Abstract</x> The inside cover picture shows Retro‐1, a benzodiazepine that blocks the retrograde transport in host cells of Shiga toxins, the virulence factors produced by pathogenic strains of E. coli responsible for food poisoning and hemolytic uremic syndrome. After synthesis and separation, the S‐enantiomer was found to be more effective at protecting human cells from Shiga toxins. For further details, see the Communication by Daniel Gillet, Jean‐Christophe Cintrat et al. on p. 1153 ff.